Book Review: VIRGINIA LEA & ERMA JEAN SIMS (EDS.). Undoing whiteness in the classroom: Critical educultural teaching approaches for social justice activism - Burkholder, Casey M. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2012)
VIRGINIA LEA & ERMA JEAN SIMS (EDS.). Undoing whiteness in the classroom: Critical educultural teaching approaches for social justice activism. New York, NY: Peter Lang. (2008). 276 pp. $35.95 (Paperback). (ISBN: 978-0-82049-712-9).